2015
DOI: 10.1371/journal.pone.0128999
|View full text |Cite
|
Sign up to set email alerts
|

Region-Based Association Test for Familial Data under Functional Linear Models

Abstract: Region-based association analysis is a more powerful tool for gene mapping than testing of individual genetic variants, particularly for rare genetic variants. The most powerful methods for regional mapping are based on the functional data analysis approach, which assumes that the regional genome of an individual may be considered as a continuous stochastic function that contains information about both linkage and linkage disequilibrium. Here, we extend this powerful approach, earlier applied only to independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…In prior studies, fixed effect functional regression models were found to outperform SKAT, its optimal unified test (SKAT‐O), and a combined sum test of rare and common variant effect (SKAT‐C) in most cases (Fan et al., , , , ,b,c; Luo et al., , , ; Svishcheva et al., ; Vsevolozhskaya et al., , ). In Fan et al.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, fixed effect functional regression models were found to outperform SKAT, its optimal unified test (SKAT‐O), and a combined sum test of rare and common variant effect (SKAT‐C) in most cases (Fan et al., , , , ,b,c; Luo et al., , , ; Svishcheva et al., ; Vsevolozhskaya et al., , ). In Fan et al.…”
Section: Discussionmentioning
confidence: 99%
“…A genotypic function is obtained by either (i) a cubic B‐spline basis expansion over a dense set of knots, κ1,...,κK, over the range of the variant's genomic positions ti's (in the one‐base coordinate system) or (ii) penalized spline smoothing that avoids the knot selection problem completely [e.g., Luo et al., , Vsevolozhskaya et al., ]. Earlier investigations of FLMs designed for genetic association testing include comprehensive coverage of the estimation procedure for the genotypic functions G(t)'s [Fan et al., , ; Lee et al., ; Luo et al., , , b; Svishcheva et al., ; Vsevolozhskaya et al., ; Wang et al., ; Zhu and Xiong, ].…”
Section: Methodsmentioning
confidence: 99%
“…As discussed elsewhere [e.g., Svishcheva et al., ; Vsevolozhskaya et al., ], statistical power of functional methods may depend on the quality of genotype data smoothing. To obtain smooth genotypic functions, we first coded allelic dosage based on the minor allele counts (i.e., either 0, 1, or 2) and applied the “flipping algorithm” [Vsevolozhskaya et al., ] to minimize the number of 0‐2 (or 2‐0) patterns in every two subsequent variant positions.…”
Section: Application To Real Data: Angprl4 Association With Tgmentioning
confidence: 99%
“…10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] In most cases, it was shown that the functional regression test statistics perform better than sequence kernel association test (SKAT), its optimal unified test (SKAT-O), and a combined sum test of rare and common variant effect (SKAT-C) of mixed models. 4,[16][17][18][19][20][21][22][23][24][25][26][27][30][31][32][33] Specifically, mixed model-based SKAT/SKATO/ SKAT-C performs well when (a) the number of causal variants is large and (b) each causal variant contributes a small amount to the traits, as the assumption of mixed models is satisfied under these circumstances. 7,21,34 In most cases, however, fixed models perform better since the causal variants of complex disorders can be common or rare or a combination of the two and some causal variants may have relatively large effects.…”
Section: Introductionmentioning
confidence: 99%
“…7,21,34 In most cases, however, fixed models perform better since the causal variants of complex disorders can be common or rare or a combination of the two and some causal variants may have relatively large effects. 10,[16][17][18][19][20][21][22][23][24][25][26][27] If the number of causal variants is large and each causal variant contributes a small amount to the traits, it would be hard to show association as the power of a test can be low. 35 One may want to note that SKAT and SKAT-O were shown to have higher power than burden tests, which is another main method to analyze rare variants.…”
Section: Introductionmentioning
confidence: 99%